Safety climate and the distracted driving experiences of truck drivers. Issue 7 (5th May 2015) - Swedler, David I.; Pollack, Keshia M.; Agnew, Jacqueline
<x xml:space="preserve">Abstract</x> Background For truck drivers, distracted driving is a workplace behavior that increases occupational injury risk. We propose safety climate as an appropriate lens through which researchers can examine occupational distracted driving. Methods Using a mixed methods study design, we surveyed truck drivers using the Safety Climate Questionnaire (SCQ) complemented by semi‐structured interviews of experts on distracted driving and truck safety. Safety climate was assessed by using the entire SCQ as an overall climate score, followed by factor analysis that identified the following safety climate factors: Communications and Procedures; Management Commitment; and Work Pressure. Results In multivariate regression, the overall safety climate scale was associated with having ever experienced a crash and/or distraction‐involved swerving. Interview participants described how these SCQ constructs could affect occupational distracted driving. Conclusion To reduce distraction‐related crashes in their organizations, management can adhere to safe policies and procedures, invest in engineering controls, and develop safer communication procedures. Am. J. Ind. Med. 58:746–755, 2015. © 2015 Wiley Periodicals, Inc.